Community Perceptions of Human-Long-Tailed Macaque Interactions in Fragmented Urban Landscapes of Palembang - Andika Imanullah; Wanda Kuswanda; Mukhlisi; Tri Atmoko; Indra Yustian (Indonesian Journal of Environmental Management and Sustainability, 2026)
Urban habitat fragmentation promotes interactions between humans and long-tailed macaques (Macaca fascicularis), creating social–ecological challenges for wildlife coexistence. Understanding community perceptions is essential for developing coexistence strategies where human activities and wildlife habitats overlap. This study evaluated community perceptions of long-tailed macaques in two fragmented landscapes, TWA Punti Kayu and Bagus Kuning, Palembang, Indonesia. A structured questionnaire was administered to 144 respondents and assessed five perception dimensions: Knowledge, Perceived Disruption Impact, Interaction Intensity, Perceived Security Risk, and Expectation for a Solution. Perception indices were calculated, while differences between locations were analyzed using the Mann–Whitney U test and relationships between perception variables and ordinal sociodemographic characteristics (age and educational level) were examined using Spearman rank correlation, whereas gender and occupation were analyzed using the Mann–Whitney U and Kruskal–Wallis H tests, respectively. Results indicated positive perceptions, with all dimensions classified as high to very high in both locations. Perceived Security Risk was the only dimension differing significantly between locations (p = 0.050), whereas Knowledge, Perceived Disruption Impact, Interaction Intensity, and Expectation for a Solution showed no significant differences (p > 0.05). Correlation analyses revealed weak associations between sociodemographic characteristics and perception variables, suggesting demographic factors played a limited role in shaping community responses. Instead, shared environmental experiences and interaction contexts appeared to exert greater influence on public perceptions. This study contributes to human-wildlife coexistence literature by integrating social and ecological perspectives. Findings demonstrate that coexistence outcomes are shaped by broader social-ecological conditions associated with habitat fragmentation and human activity patterns. Results emphasize site-specific management, including education, feeding regulation, waste management, community engagement, and urban biodiversity planning, to support sustainable human–macaque coexistence.